Computer and Information Science - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the outcomes of the 17th IEEE/ACIS International Conference on Computer and Information Science (ICIS 2018), which was held in Singapore on June 6-8, 2018. The aim of the conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the various fields of computer science and to share their experiences, and to exchange new ideas and information in a meaningful way. The book includes findings on all aspects (theory, applications and tools) of computer and information science and discusses related practical challenges and the solutions adopted to solve them. The conference organizers selected the best papers from those accepted for presentation. The papers were chosen based on review scores submitted by members of the program committee and underwent a further rigorous round of review. From this second round, 13 of the conference's most promising papers were then published in this Springer (SCI) book and not the conference proceedings. We impatiently await the important contributions that we know these authors will make to the field of computer and information science.
The Analysis of the Appropriateness of Information Education Curriculum Standard Model for Elementary School in Korea -- New Gene Selection Method Using Gene Expression Programing Approach on Microarray Data Sets -- A Novel Differential Selection Method based on Singular Value Decomposition Entropy for Solving Real-World Problems -- Power Consumption Aware Machine Learning Attack for Feed-Forward Arbiter PUF -- Adaptive Generative Initialisation in TransferLearning -- A Multicriteria Group Decision Making Approach for Evaluating Renewable Power Generation Sources -- Incremental Singular Value Decomposition Using Extended Power Method -- Personalized Landmark Recommendation for Language-specific Users by Open Data Mining -- Joint Radio Resource Allocation in LTE-A Relay Networks with Carrier Aggregation.
Keywords: Computational intelligence; Artificial intelligence; Business information services; Computer networks .; Electronic data processing -- Management; Computational Intelligence; Artificial Intelligence; Business Information Systems; Computer Communication Networks; IT Operations